1959
DOI: 10.1126/science.129.3357.1226
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Brain Barrier for Adrenaline

Abstract: The concentration of tritiumlabeled adrenaline was determined in various areas of cat brain after intravenous infusion. It did not exceed that expected from the blood content of the tissue except in the hypothalamus, where small but significant amounts of H(3)-adrenaline were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0
1

Year Published

1960
1960
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 292 publications
(76 citation statements)
references
References 9 publications
0
75
0
1
Order By: Relevance
“…First, unlike MP that penetrates the blood brain barrier (BBB), epinephrine which does not readily cross the BBB (Weil-Malherbe et al, 1959) induced the same dimorphic effects (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, unlike MP that penetrates the blood brain barrier (BBB), epinephrine which does not readily cross the BBB (Weil-Malherbe et al, 1959) induced the same dimorphic effects (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…Design and procedure-To learn whether the crossing of the blood-brain barrier by MP is a factor in the above observed male -female differences, a direct comparison of the impact of MP to the impact of epinephrine (of virtually no brain availability [Weil-Malherbe et al, 1959]) was undertaken in mature animals. A 2×3 experimental design was used in which mature males and females were assigned to receive MP (0.8 mg/kg), epinephrine (0.6 mg/kg), or vehicle injection 1 h before MADB106 tumor inoculation, n = 111 animals.…”
Section: Methodsmentioning
confidence: 99%
“…Because of the low endogenous levels of epinephrine and norepinephrine in urine, it was necessary to use [ 3 H]epinephrine into cats, it persisted unchanged for at least 2 h in heart, spleen, and salivary gland long after the physiological effects were ended (32). We also found the [ 3 H]epinephrine did not cross the blood-brain barrier (33). [ 3 H]Epinephrine and [ 3 H]norepinephrine were concentrated in organs rich in sympathetic nerves (heart, spleen, and salivary gland).…”
Section: Inactivation Of Neurotransmitters By Uptake In Nerve Terminalsmentioning
confidence: 73%
“…Because catecholamines do not cross the blood-brain barrier (33) it was impossible to study the uptake, metabolism, storage, and release of catecholamine in the brain. Jacques Glowinski, a postdoctoral fellow, devised a technique to introduce [ 3 H]norepinephrine directly into the rat brain by injection into the lateral ventricle.…”
Section: Reflections: Late Blooming Biochemical Neuroscientistmentioning
confidence: 99%
“…The facts that L-tyrosine is a relatively poor substrate for this enzyme (Lovenberg et al 1962) and that human brain is characterized by highly variable enzyme activity (Sacks et al 1979) provide a likely explanation for the capricious nature of the clinical response to L-tyrosine. Although polar compounds like tyramine are traditionally unable to cross the blood-brain barrier (Weil-Malherbe et al 1959), we cannot rule out the possibility that tyramine traverses this barrier in low concentration, to a degree varying from individual to individual. The single case study of Pickar et al (1979) may well be instructive in this regard: they found that the intravenous administration of tyramine to a patient with bipolar affective disorder led to a lightening of affect.…”
mentioning
confidence: 99%